Problematika Valuasi Hak Cipta Sebagai Objek Jaminan Fidusia - Mayang Sari, Putri (UNES Law Review, 2023)
Copyright is an intangible movable object that can be used as an object of fiduciary security. However, in practice, we still encounter obstacles due to assessment issues, even though the government, through Government Regulation Number 24 of 2022, has issued regulations that can encourage the implementation of copyright guarantees as an object of credit collateral. This paper examines how the assessment can be done to determine the copyright that can be used as an object of fiduciary guarantee and how the role of the public appraiser to determine the value of the object of fiduciary guarantee in the form of copyright. The research method used in writing this scientific article is normative juridical research which is supported by data sourced from interviews, review of statutory regulations and literature study. The research results show that the assessment of copyright as a collateral object consists of 4 (four) approaches, namely the cost approach, market approach, income approach, and other assessment approaches in accordance with assessment standards. The legal position of public appraisers in assessing intellectual property is regulated in Minister of Finance Regulation Number 101/PMK.01/2014 concerning Public Appraisers as well as the legitimacy of public appraisers to assess copyright as an object of fiduciary guarantees as regulated in Government Regulation Number 24 of 2022 concerning Law Implementation Regulations -invite. Law Number 24 of 2019 concerning Creative Economy.